The factors affecting job motivation of university employees and its relationship with health factors at workplace - Mehran Nazari; Saeed Sayadi; Masoud Pourkiani; Mohammad Jalal Kamali (Shahid Beheshti University of Medical Sciences, 2023)
Background: Job motivation of workforce is one of the most important issues that organizations face to perform their tasks and duties well and with confidence and maintain their effectiveness. Methods: The present study was applied research conducted by using a combination of library studies and Delphi technique. The sample size of the present study was 332 employees of Islamic Azad University of Khuzestan. They were selected using Cochran's formula. Two researcher-made questionnaires including job motivation questionnaire with 54 questions and health factors questionnaire with 30 questions were used to collect the data. The collected data were analyzed by SPSS-22, Lisrel, and Amos-22 Software. Results: The variable of factors related to job motivation consisted of 15 components. The variable of job motivation in general found that according to the scoring scale of Abbas Bazargan, this variable is at more than satisfactory level. The variable of health factors was at more than satisfactory level. There was significant association between job motivation with health factors (P<0.001). Relationship between job motivation and health factors showed that direct and significant relationship between job motivation with health factors. The value of path coefficient of impact of health factors on job motivation showed that the relationship between job motivation and health factors is significant. Conclusion: Job motivation is a multidimensional phenomenon that cannot be measured directly by one variable. One of the important tasks of organizations is finding the ways to create and strengthen motivation. Managers should consider motivating employees as one of the most important tasks.